Poly(ADP-ribosyl)ation mediates early phase histone eviction at DNA lesions. Issue 6 (22nd January 2020) - Yang, Guang; Chen, Yibin; Wu, Jiaxue; Chen, Shih-Hsun; Liu, Xiuhua; Singh, Anup Kumar; Yu, Xiaochun
Abstract: Nucleosomal histones are barriers to the DNA repair process particularly at DNA double-strand breaks (DSBs). However, the molecular mechanism by which these histone barriers are removed from the sites of DNA damage remains elusive. Here, we have generated a single specific inducible DSB in the cells and systematically examined the histone removal process at the DNA lesion. We found that histone removal occurred immediately following DNA damage and could extend up to a range of few kilobases from the lesion. To examine the molecular mechanism underlying DNA damage-induced histone removal, we screened histone modifications and found that histone ADP-ribosylation was associated with histone removal at DNA lesions. PARP inhibitor treatment suppressed the immediate histone eviction at DNA lesions. Moreover, we examined histone chaperones and found that the FACT complex recognized ADP-ribosylated histones and mediated the removal of histones in response to DNA damage. Taken together, our results reveal a pathway that regulates early histone barrier removal at DNA lesions. It may also explain the mechanism by which PARP inhibitor regulates early DNA damage repair.